PSI-29 Effect of hydrolysable tannin with or without condensed tannin on animal performance and methane emission of beef cattle fed a high forage diet. (7th December 2018) - Aboagye, I; Oba, M; Castillo, A; Koenig, K; Beauchemin, K
Abstract: The long-term effect of hydrolysable tannin (HT) with or without condensed tannin (CT) on animal performance and methane (CH4) production in beef cattle fed a high forage diet was examined. Seventy-five crossbred steers (292 ± 4.1 kg), blocked by body weight (BW) and penned individually were randomly assigned to one of five dietary treatments (15 animals/treatment) in a randomized complete block design. Animals received a basal diet of alfalfa:barley silages [50:50; dry matter (DM) basis] of crude protein content 170 g/kg as the control (no tannin), supplemented with 0.25% chestnut (CN), 1.5% CN, combination of CN and quebracho (Q) at 0.125% each (0.25% CNQ), or at 0.75% each (1.5% CNQ) of dietary DM. Treatments for CH4 measurement were: control, 1.5% CN and 1.5% CNQ. Animal performance, rumen fermentation (oral sampling) and nitrogen (N) utilization measurements lasted for 84 d; thereafter 30 d was used to measure CH4 emissions using a tracer gas technique. The DM intake (DMI), BW, average daily gain, and gain:feed were not affected (P ≥ 0.10) by treatment. Tannins irrespective of type or dose reduced (P = 0.01) rumen ammonia concentration. Blood urea N concentration of animals fed tannin at 1.5% CN or CNQ was greater (P = 0.047) compared with 0.25% CNQ (121 vs. 112 mg N/L). Tannin type or dose did not affect (P ≥ 0.54) daily CH4 produced (154 ± 5.9 g/d) but at 1.5% CNQ, CH4 yield tended (P = 0.09) to reduce compared with control (20.6 vs. 22.0 g/kg DMI). Hydrolysable tannin with or without CT can be added to a high forage diet at 0.25 or 1.5% dietary DM without adverse effect on animal performance while reducing rumen ammonia concentration. A combination of HT and CT at 1.5% dietary DM showed a tendency to reduce CH4 emissions of growing beef cattle.